India and the WTO - Mattoo, Aaditya; Stern, Robert M. (Washington, DC: World Bank and Oxford University Press, 2013)
India's trade policy establishment is perceived to be somewhat wary of multilateral engagement, even though India is implementing substantial economic, and trade policy reforms. Some essays in this well-researched volume may throw light on this paradox. More important, the essays take a hard look at India's interests, and concerns with respect to international trade. They suggest ways that India could deploy its domestic reform agenda in the Doha Round negotiations, to secure concessions from its trading partners, while using multilateral engagement to reinforce the domestic reform process, and enhance the process' credibility. The book should prove of considerable value to policymakers, market participants, and other stakeholders.